Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1029/2021jd036168
|View full text |Cite
|
Sign up to set email alerts
|

The Sources, Molecular Compositions, and Light Absorption Properties of Water‐Soluble Organic Carbon in Marine Aerosols From South China Sea to the Eastern Indian Ocean

Abstract: Water-soluble organic carbon (WSOC) is a major component of marine organic aerosols (Bao et al., 2018;Srinivas & Sarin, 2013), which can influence the regional climate by exerting both direct and indirect effects. On the one hand, WSOC can alter the hygroscopicity of aerosol particles and their ability to act as cloud condensation nuclei (CCN), thus contributing to indirect aerosol climate effects (Huang, Ickes et al., 2018). On the other hand, a certain fraction of WSOC also exhibits light-absorbing (brown ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Therefore, most of the literature cited above has chosen the similar wavelength bands to make the comparisons more reliable. In a previous study, Mo et al (2022) reported a good linear correlation between MAE 365 and AAE, despite fitting AAE with different wavelength. This indicates that the aromatic component in WSOC is a crucial factor in determining its light absorption capacity.…”
Section: Uv-vis Light Absorption Properties Of Ws-brcmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, most of the literature cited above has chosen the similar wavelength bands to make the comparisons more reliable. In a previous study, Mo et al (2022) reported a good linear correlation between MAE 365 and AAE, despite fitting AAE with different wavelength. This indicates that the aromatic component in WSOC is a crucial factor in determining its light absorption capacity.…”
Section: Uv-vis Light Absorption Properties Of Ws-brcmentioning
confidence: 87%
“…As shown in Supplementary Figure S1, during the autumn campaign, most air masses originated from the northern continent, but in summer, only a small fraction originated from the continent, while the majority came from the ocean. Continent-influenced air masses carried substances that absorb light stronger than marine-influenced air masses (Mo et al, 2022;Tang et al, 2024).…”
Section: Uv-vis Light Absorption Properties Of Ws-brcmentioning
confidence: 99%
“…Field blanks were subtracted from the spectra of the extracts. The light‐absorption coefficients of WSOC and MSOC at 365 nm (Abs 365,WSOC and Abs 365,MSOC ) were used as BrC proxies according to previous studies, and the detailed calculations are presented in Text S2 of Supporting Information (Hecobian et al., 2010; Mo et al., 2022). Water‐insoluble organic carbon (WISOC) was then defined as the difference between MSOC and WSOC.…”
Section: Methodsmentioning
confidence: 99%
“…Water‐soluble organic carbon (WSOC) typically constitutes up to 70% of total OC and 53%–66% of total absorption at 300–400 nm (Chen et al., 2017; Mo et al., 2022), excluding BC interference. When biomass combustion is absent, WSOC is usually considered as a surrogate for SOA (Weber et al., 2007).…”
Section: Introductionmentioning
confidence: 99%